Capsule Ablator Inflight Performance Measurements Via Streaked Radiography Of ICF Implosions On The NIF*. (March 2016) - Dewald, E L; Tommasini, R; Mackinnon, A; MacPhee, A; Meezan, N; Olson, R; Hicks, D; LePape, S; Izumi, N; Fournier, K; Barrios, M A; Ross, S; et al.
Abstract: Streaked 1-dimensional (slit imaging) radiography of 1.1 mm radius capsules in ignition hohlraums was recently introduced on the National Ignition Facility (NIF) and gives an inflight continuous record of capsule ablator implosion velocities, shell thickness and remaining mass in the last 3-5 ns before peak implosion time. The high quality data delivers good accuracy in implosion metrics that meets our requirements for ignition and agrees with recently introduced 2-dimensional pinhole radiography. Calculations match measured trajectory across various capsule designs and laser drives when the peak laser power is reduced by 20%. Furthermore, calculations matching measured trajectories give also good agreement in ablator shell thickness and remaining mass.